A multi-institutional study of secondary check of treatment planning using Clarkson-based dose calculation for three-dimensional radiotherapy. (May 2018) - Takahashi, Ryo; Kamima, Tatsuya; Itano, Masanobu; Yamazaki, Takeshi; Ishibashi, Satoru; Higuchi, Yoshihiro; Shimizu, Hiroyuki; Yamamoto, Toshijiro; Yamashita, Mikiko; Baba, Hiromi; Sugawara, Yasuharu; Sato, Aya; et al.
Highlights: Clarkson-based dose calculation verification is common for secondary plan checks. There have been few reports on the verification of large cohorts of patients. A total of 5936 fields were collected and analyzed in a multi-institutional study. A 3–5% limit may be feasible as an action level per our quantitative analysis. Care must be taken when determining an institution-specific action level. Abstract: Purpose: As there have been few reports on quantitative analysis of inter-institutional results for independent monitor unit (MU) verification, we performed a multi-institutional study of verification to show the feasibility of applying the 3–5% action levels used in the U.S. and Europe, and also to show the results of inter-institutional comparisons. Methods: A total of 5936 fields were collected from 12 institutions. We used commercial software employing the Clarkson algorithm for verification after a validation study of measurement and software comparisons was performed. The doses generated by the treatment planning systems (TPSs) were retrospectively analyzed using the verification software. Results: Mean ± two standard deviations of all locations were 1.0 ± 3.6%. There were larger differences for breast (4.0 ± 4.0%) and for lung (2.5 ± 5.8%). A total of 80% of the fields with differences over 5% of the action level involved breast and lung targets, with 7.2 ± 5.4%. Inter-institutional comparisons showed various systematic differences for field shape for breast and differences in the fields were attributable to differences in reference point placement for lung. The large differences for breast and lung are partially attributable to differences in the methods used to correct for heterogeneity. Conclusions: The 5% action level may be feasible for verification; however, an understanding of larger differences in breast and lung plans is important in clinical practice. Based on the inter-institutional comparisons, care must be taken when determining an institution-specific action level from plans with different field shape settings and incorrectly placed reference points.